СУЧАСНИЙ СТАН СТВОРЕННЯ, ВИРОБНИЦТВА ТА ДОСЛІДЖЕННЯ ТАБЛЕТОВАНИХ ЛІКАРСЬКИХ ПРЕПАРАТІВ Повідомлення 19. Сучасний стан розробки та дослідження мультипартикулярних пелетних систем. - Демчук, М. Б.; Гуреєва, С. М.; Грошовий, Т. А. (Фармацевтичний часопис, 2015)
MODERN STATE OF CREATION, PRODUCTION AND RESEARCH OF DRUGS M.B. Demchuk, S.M. Gureyeva1, T.A. Hroshovyi TernopilStateMedicalUniversityby I.Ya. Horbachevsky 1JSC “Farmak” Notice 19. The current state of development and research of multiple unit pellet systems. Summary: the literature on technological aspects of creations of pellets, features of compression pellet to obtain multiple unit pellet systems are summarized. Keywords: pellets, methods of pellets, pellet pressing, multiple unit pellet systems. Introduction. Oral modified-release multiple-unit dosage forms have always been more effective therapeutic alternative to conventional or immediate release single-unit dosage forms. With regards to the final dosage form, the multiparticulates are usually formulated into single-unit dosage forms such as filling them into hard gelatin capsules or compressing them into tablets. Pelletization is a technique that enables the formation of spherical beads or pellets with a mean diameter usually ranging from 0.5 to2.0 mm. These pellets can evantually be coated and very often used in controlled-release dosage forms. The use of pelletization and pellets leads to an improvement in the flowability, appearance and mixing properties, thus avoiding excessive dust and reducing segregation and, generally, eliminating undesirable properties and improving the physical or chemical properties of fine powders. The pharmaceutical industry has developed a great interest in pelletization due to a variety of reasons: – prevention of segregation of co-agglomerated components, resulting in an improvement of the uniformity of the content; – prevention of dust formation; – increasing bulk density and decreasing bulk volume; – the defined shape and weight improves the appearance of the product; – improvement of the handling properties, due to the free-flowing properties; – improvement of the hardness and friability of pellets; – controlled release application of pellets due to the ideal low surface area-to-volume ratio that provides an ideal shape for the application of film coatings. Pellets are prepared by different techniques, such as extrusion and spheronisation, rotogranulation, solution, suspension or powder layering, spray-drying or spray-congealing. Extrusion / spheronisation is a multistage process for obtaining pellets with uniform size from wet granulates (extrudates). The process is more labour-intensive and more expensive than the conventional wet-granulation technique, as its use should be limited only to the production of spherical pellets for controlled release of drugs. The fluid-bed granulation consists in the spraying of a granulation solution onto the suspended particles, which then are dried rapidly in the hot air stream. Rotogranulation is one of the most recent methods for the production of spheroids. The single-unit spheronizing system can be described using terms like centrifugal granulator, rotary fluidized-bed granulator, rotary fluid bed, rotary processor or rotor granulator. Layering a suspension or a solution of a drug on a seed material (usually, a coarse crystal or nonpareil) can produce pellets that are uniform in size distribution and generally posess very good surphace morphology. These characteristics are especially desirable when pellets will be coated for the purpose of achieving a controlled release. Dry powder layering is similar to the solution or suspension layering. Instead of these dispersions, the layering is performed using a drug powder. Spray-drying represents another process with limited application in the development of pharmaceutical pelletized products, based on globulation. During spray-drying, a drug solution or suspension is sprayed, with or without excipients, into a hot-air stream, generating dry and highly spherical particles. Spray-congealing (spray-chilling) is a technique similar to spray-drying. Spray-congealing is a process in which a drug is allowed to melt, disperse or dissolve in hot melts of gums, waxes, fatty acids or other melting solids. The dispersion is then sprayed into a stream of air and other gases with a temperature below the melting point of the formulation components. Conclusions. The basic requirements and approaches to development multiple unit pellet system, aspects and examples receipt of pellets and tablets based on them are described.